Analisis Kelayakan Usaha Unit Pengelola Jasa Mesin Penanam Padi (Rice Transplanter) Di Kabupaten Ponorogo - Lutfiana Ulfa (Manajemen Agribisnis: Jurnal Agribisnis, 2021)
This study aims to describe the level of adoption of rice transplanter technology and analyze the financial feasibility of the rice transplanter rice planting machine business unit in Ponorogo Regency. The research location was chosen purposively in four sub-districts in Ponorogo Regency which has a business unit as well as a manager of rice transplants with three different years of machine investment, namely in 2017, 2018 and 2019. This study uses mix methods for get qualitative data then followed by quantitative data. The results showed that: Both interpersonal and group communication channels greatly influenced the adoption rate. The more farmers take the initiative to actively seek information, be open in groups and socially, the faster the adoption process of ricetransplanter. No farmers found in the category of Late Majority because farmers who are members of Gapoktan (actively seeking and getting information) will immediately adopt technology and farmers who are not affiliated with Gapoktan will reject this technology and fall into the laggards category. The Ricetransplanter Planting Machine business unit is financially feasible and partly unfeasible, shown by the Net Present Value (IRR) (Net Rate of Return) Gross B / C (Gross Benefit Cost Ratio) Net B / C (Net Benefit Cost Ratio ) and PP (Payback Period) are attached from the economic life of the machine for fifteen years.